Analisis Faktor – Faktor yang mempengaruhi Profitabilitas Bank Umum di Indonesia - Soetjiati Soetjiati; Rimi Gusliana Mais (Jurnal Manajemen, 2019)
: This thesis aims to provide an overview of the effects of Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (BOPO), Non Performing Loans (NPL), Net Interest Margin (NIM), Loan Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) ) partially or simultaneously on the performance of state-owned banks in Indonesia as measured by the ratio of Return on Assets (ROA). This Research uses a correlational type of study with a quantitave approach. The statistical tests used are descriptive statistics, Determination of estimation models, and hypothesis testing with the help of Eviews 9.0 software. The population in this study were 4 state-owned banks. Research Samples are all state-owned banks in Indonesia in the 2014-2018 period in the form of quarterly data. The Fixed Effect Model Results are The Capital Adequacy Ratio has a negative effect on the performance of state-owned banks in Indonesia, which was proxied by Return on Assets (ROA), so H1 was rejected. Operating Expenses Operating income has a negative effect on the performance of state-owned banks in Indonesia, which is proxied by Return on Assets (ROA), so that H2 is received. Non Performing Loans have no effect on the performance of state-owned banks in Indonesia which are proxied by Return on Assets (ROA), so H3 is rejected. Net Interest Margin has a positive effect on the performance of state-owned banks in Indonesia, which is proxied by Return on Assets (ROA), so that H4 is accepted. Loan to Deposits Ratio has a positive effect on the performance of state-owned banks in Indonesia, which is proxied by Return on Assets (ROA), so that H5 is accepted. The results of the F Capital Adequacy Ratio (CAR) Test, Operational Income Operating Expenses (BOPO), Non Performing Loans (NPL), Net Intererst Margin (NIM) and Loan Deposit (LDR) simultaneously affect the performance of BUMN banks in Indonesia as measured by the ratio Return on Assets (ROA), so H6 is accepted